2008
DOI: 10.1097/pcc.0b013e3181668c22
|View full text |Cite
|
Sign up to set email alerts
|

Glucose control, organ failure, and mortality in pediatric intensive care*

Abstract: Hyperglycemia is common in PICUs, occurs early, and is independently associated with organ failure and death. However, early hyperglycemia is not associated with later or worsening organ failure. Australasian PICUs seldom use insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
2
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 31 publications
1
61
2
8
Order By: Relevance
“…Several studies have shown an association between glucose and poor outcome in children admitted for both medical and surgical treatment in the PICU. 5,15,[36][37][38][39][40] Numerous mechanisms for this association have been proposed, including increased inflammatory cytokine production, acute endothelial dysfunction, hypercoagulation, metabolic disturbances, and increased cellular apoptosis. 41 While the exact benefit of using insulin therapy remains in question, use of nutritional interventions along with insulin to maintain normoglycemia does appear to be protective.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an association between glucose and poor outcome in children admitted for both medical and surgical treatment in the PICU. 5,15,[36][37][38][39][40] Numerous mechanisms for this association have been proposed, including increased inflammatory cytokine production, acute endothelial dysfunction, hypercoagulation, metabolic disturbances, and increased cellular apoptosis. 41 While the exact benefit of using insulin therapy remains in question, use of nutritional interventions along with insulin to maintain normoglycemia does appear to be protective.…”
Section: Discussionmentioning
confidence: 99%
“…30 Skor PELOD hanya dilakukan satu kali yaitu saat masuk PICU. Leteurtre dkk 30 membagi skor PELOD yang dilakukan pada hari pertama menjadi 3 kelompok, yaitu rendah (< 10), sedang (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), dan tinggi (>20), dengan nilai cut-off 10 dan 20 berhubungan dengan peningkatan mortalitas. Kami juga menggunakan nilai cut-off skor PELOD 20 dan didapatkan 10 subjek yang memiliki nilai PELOD >20.…”
Section: Hubungan Antara Hiperglikemia Dan Luaranunclassified
“…Kelompok pasien yang mengalami hiperglikemia stres memiliki lama pemakaian ventilasi mekanik dan penggunaan inotropik yang lebih panjang, [11][12][13] serta derajat disfungsi organ yang lebih berat. 12,14,15 Dari pengamatan sering ditemukan keadaan hiperglikemia pada anak yang sakit berat. Di Indonesia, baru satu penelitian kecil dengan 15 subjek oleh Nurnaningsih dkk 2 yang meneliti kondisi hiperglikemia pada anak dengan perawatan intensif di PICU, dan mencari korelasi hiperglikemia dengan derajat disfungsi organ.…”
unclassified
“…O segundo estudo de coorte prospectivo analisado foi recentemente publicado em 2008 por Yung et al 13 e incluíram 409 crianças internadas em UTIP e em ventilação pulmonar mecâ-nica por mais de 12 horas. Yung et al 13 publicaram, em 2008, estudo de coorte prospectivo reunindo nove UTIs pediátricas na Austrália e Nova Zelândia e analisaram crianças em VPM por mais de 12 horas, excluindo as com diagnóstico de cetoacidose diabética, em ventilação domiciliar, com procedimentos cirúr-gicos cardíacos e com ordens de não reanimação.Estabelecidos cortes para definição de hiperglicemia em 110 e 126 mg/dL e os desfechos avaliado foram a relação entre hiperglicemia e o escore pediátrico de disfunção orgânica (PELOD) e com a mortalidade.…”
Section: Hiperglicemia E Pacientes Em Uti Pediátrica Geralunclassified
“…Yung et al 13 publicaram, em 2008, estudo de coorte prospectivo reunindo nove UTIs pediátricas na Austrália e Nova Zelândia e analisaram crianças em VPM por mais de 12 horas, excluindo as com diagnóstico de cetoacidose diabética, em ventilação domiciliar, com procedimentos cirúr-gicos cardíacos e com ordens de não reanimação.Estabelecidos cortes para definição de hiperglicemia em 110 e 126 mg/dL e os desfechos avaliado foram a relação entre hiperglicemia e o escore pediátrico de disfunção orgânica (PELOD) e com a mortalidade. A análise univariada mostrou que a hiperglicemia esteve associada ao escore maior que 10 com razão de chances de 3,4 (intervalo de confiança -IC -95% entre 1,85-6,46 e nível de significância "p" < 0,0001) e associada à mortalidade com razão de 3,12 (IC 95% 1,26-7,7 com p < 0,001).…”
Section: Hiperglicemia E Pacientes Em Uti Pediátrica Geralunclassified